India’s Sports Transformation for Viksit Bharat@2047 - Ramesh S. Nagaraddi; H.S. Jange (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
India’s vision of becoming a developed nation by 2047, referred to as Viksit Bharat @ 2047, necessitates a comprehensive transformation across multiple sectors, including education, technology, economy, and healthcare. Among these, sports represent a unique and powerful domain that connects physical health, cultural identity, youth engagement, and global prestige. This paper examines India’s current sports ecosystem and outlines a roadmap for transformation into a globally competitive sports power by 2047. Drawing from comparative international models, government initiatives, and socio-economic analysis, the paper identifies seven key pillars of transformation: grassroots development, infrastructure and sports science, sports economy and industry, Olympic and global excellence, inclusivity and empowerment, digital sports innovation, and fitness culture. The study argues that by mainstreaming sports as both an economic driver and a cultural necessity, India can achieve not only sporting excellence but also broader national development goals. Projecting a future where sports contribute 5–6% of India’s GDP, create millions of jobs, and position India among the top five sporting nations, this paper establishes sports as an integral pillar of Viksit Bharat @ 2047.